Eyelid fissure dimensions in Japanese and in Brazilians of European descent over 50 years of age - Hata Viveiros, Magda Massae [UNESP]; Matai, Olivia [UNESP]; Takahagi, Rodrigo Ueno [UNESP]; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana Artioli [UNESP] (Consel Brasil Oftalmologia, 2017)
Purpose: To investigate differences in the palpebral fissure eyelid position in Japanese subjects and in Brazilian subjects of European descent over 50 years of age. Methods: A cross-sectional study evaluating 50 Japanese subjects and 50 Brazilian subjects of European descent over 50 years of age was performed to evaluate the effect of aging on eyelid position. Digital photographs were taken with the eyes in the primary position and transferred to a computer to be processed by Scion imaging software for evaluation of palpebral fissure width, height, and margin reflex distance (MRD). The data were statistically analyzed according to sex, age, and race. Results: The width of the eyelid fissure in Japanese subjects was higher than that in Brazilian subjects, whereas the height of the eyelid fissure and the MRD1 was higher in Brazilians than in Japanese (p<0.01). Width, height, and MRD1 were linearly associated with age only in the Japanese group (p<0.05); this association was observed only with width in the Brazilian group (p<0.05). There were no differences according to laterality in either group (p>0.05). Conclusion: There are racial differences in age-related changes in the eyelids, which are more marked in Japanese subjects.
Keywords: Eyelids/anatomy and histology; Eyelids/pathology; Asian Continental Ancestry Group; Brazilian; Age factors; Image processing, computer-assisted